ANALISIS PERBANDINGAN KINERJA KEUANGAN BADAN USAHA MILIK DESA (BUMDES) DI KABUPATEN ROKAN HULU - Afrijal, Ramadhani (Jurnal Ilmiah Cano Ekonomos, 2017)
This study aimed to analyze the financial performance of Badan Usaha Milik Desa (BUMDes) in Rokan Hulu district using financial ratios choice. In analyzing the data obtained, the method used is descriptive analysis and comparative analysis. Descriptive analysis using financial ratio analysis method is selected while a comparative analysis was used to compare the financial performance BUMDes in Rokan Hulu in 2014 in accordance with the results of the calculation of financial ratios. Based on the results of the study showed that the average current ratio BUMDes in Rokan Hulu by 277% (very good). Average Debt to Asset Ratio (DAR) by 42% (good). The average ratios Return on Assets (ROA) of 8% (good). The average ratio of Total Asset Tun Over (TATO) of 0.23 times (not good).